0659 Effects of BMI and Fragmentation of The Activity Rhythm Across The Sleep-Wake Cycle on The Work Performance. (27th April 2018) - Marot, L P; Rosa, D; Crispim, C A
Abstract: Introduction: Shift workers often redistribute food intake from the daytime to the night hours, which is associated with weight gain and obesity. Fragmentation of the activity rhythm across the sleep-wake cycle is also associated with shift work. The objective of this study was to evaluate the influence of shift rotation, BMI and the fragmentation of rest- activity rhythm (Intradaily Variability; IV) on the lapses of attention among shift workers. Methods: The study included 30 males shift workers. The rotation of shift work schedule was carried out as follow: two days during the day; two days during the afternoon; 24h free-day; two days during the night and 72h off. The preliminary evaluations involved a questionnaire with sociodemographic characteristics and health habits, evaluation of height, weight was used for the done to assessed BMI estimation. The vigilance level was measured using the Psychomotor Vigilance Test (PVT) throughout the schedule shift. The use of actigraphy registered the rest-activity rhythm and estimated the IV. The number of lapses progression was evaluated using Generalized Estimating Equations (GEE). Spearman's correlation was used to evaluate the relationship between IV and BMI. Results: We found a significant effect of the BMI and IV on number of lapses (eutrophic individuals presented a smaller number of lapses than excessive body weight and little fragmented individuals presented a smaller number of lapses than higher fragmented). The values of IV was positively associated with BMI. Conclusion: Excessive BMI and higher value of IV influence on lapses throughout the shift rotation and negatively impact the work performance. Support (If Any): FAPEMIG and CAPES.